Analisis Pemanfaatan Media Energi Putar Sederhana pada Materi Energi Kelas 4 di SDN Karangrejo 01 Jember - Elmi Hildania; Yunda Dewi Respati; Ulfatul Rofida; Muhammad Suwignyo Prayogo (Universitas Palangka Raya, 2025)
This study aims to analyze the use of a simple rotating energy medium, a mini windmill, in Natural and Social Sciences (IPAS) learning on Energy and Its Transformations in fourth-grade students at SDN Karangrejo 01 Jember. The research approach used was descriptive qualitative, involving teachers and fourth-grade students as research subjects. Data were collected through observations during learning activities, interviews with teachers regarding learning strategies and student responses, and documentation in the form of photographs, learning outcomes notes, and student worksheets. The results showed that the use of a mini windmill provided a concrete and easily understood learning experience for students. This medium helped students directly observe the process of energy conversion from wind energy to kinetic energy, thus enhancing the concept learned through abstraction. Furthermore, students appeared more enthusiastic, actively engaged in discussions, and were able to provide examples of energy transformations in everyday life. Thus, the use of a simple rotating energy medium has proven effective in enhancing understanding of energy concepts in elementary school IPAS learning.